HUBUNGAN ANTARA KESEIMBANGAN DAN KEKUATAN OTOT TUNGKAI DALAM PENINGKATAN POLA KECEPATAN TENDANGAN A PADA ATLET SILAT DI PSHT CABANG PANCORAN JAKARTA - Yulis Susanti; Ikhwanul Mirza (CV. Adiba Aisha Amira, 2025)
Pencak Silat, as a martial art, involves techniques for attacking, evading, catching, and throwing opponents. The speed of executing a kick is an important aspect for a pesilat, one of which is the A-kick using the toes with a straight leg. The ability to launch a kick quickly is highly dependent on balance and leg muscle strength. This study aims to determine the relationship between balance and leg muscle strength with the speed of the A-kick in athletes of Persaudaraan Setia Hati Terate, Pancoran branch. This study uses a cross-sectional method with chi-square testing for data analysis. The results show a significant relationship between balance and A-kick speed with a p value of <0.05 (0.007), as well as between leg muscle strength and A-kick speed with a p value of <0.05 (0.017). Therefore, H0 is rejected and it can be concluded that there is a relationship between balance and leg muscle strength with the speed of the A-kick in Persaudaraan Setia Hati Terate athletes in Pancoran branch.